IMPORTANCE OF USING AUTHENTIC MATERIALS IN TEACHING ENGLISH - Jalolidinova Saodatxon Anvarbek qizi; Umaraliyeva Munojatxon Mashrabovna (Лучшие интеллектуальные исследования, 2024)
Abstract: This article highlights the importance of using authentic materials in teaching English. Using authentic materials during the lesson makes lessons more interesting and engaging for students. Materials that are taken from the real world and not specially designed for educational purposes are considered authentic materials in teaching. As they create a natural atmosphere, authentic materials facilitate students’ understanding of the world and their communicative competence.